Shared pain: the meaning of the Compassio Mariae in the visual culture of the thirteenth century - García Morales , Julia María (Eikón / Imago, 2025)
The present research deals with the meaning of the Virgin's compassion. This, understood as a shared emotion, had already been raised in various medieval medical treatises, but also in the theological framework, where it was linked to the figure of the Mother of God. Her compassion became a powerful meditative tool in the devotional practices of the late Middle Ages and became a model example for the faithful. This was understood as the physical and mental passion she suffered with her own son during the Passion. Pain, expressed through visual formulas such as fainting, permeated all kinds of compositions throughout the 13th century: artistic, literary, liturgical, musical, etc.